2022
DOI: 10.1021/jacs.2c01456
|View full text |Cite
|
Sign up to set email alerts
|

Al3+ Dopants Induced Mg2+ Vacancies Stabilizing Single-Atom Cu Catalyst for Efficient Free-Radical Hydrophosphinylation of Alkenes

Abstract: Utilizing heterogeneous catalysts to overcome obstacles for homogeneous reactions is fascinating but very challenging owing to the difficult fabrication of such catalysts based on the character of target reactions. Herein, we report a Al 3+ doping strategy to construct single-atom Cu on MgO nanosheets (Cu 1 /MgO(Al)) for boosting the free-radical hydrophosphinylation of alkenes. Al 3+ dopants in MgO bring about abundant Mg 2+ vacancies for stabilizing dense independent Cu atoms (6.3 wt %), while aggregated Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…This indicated that the active metal Pd and Al species were highly S2), further confirming the formation of the Zn vacancies. 25 Furthermore, Al 3+ doping can induce Zn 2+ vacancies in ZnO, which reduces the electron density of Zn and O due to charge neutrality (Figure 4d). 25,38 Clearly, the Pd 3d 5/2 spectrum showed that the active metal existed in the form of Pd 2+ and was slightly shifted to a higher binding energy for 0.4% Pd/Zn(Al)O (10:1) (Figure 4e), possibly due to the metal−support interaction between the Pd and Pd/Zn(Al)O resulting from the metal vacancies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This indicated that the active metal Pd and Al species were highly S2), further confirming the formation of the Zn vacancies. 25 Furthermore, Al 3+ doping can induce Zn 2+ vacancies in ZnO, which reduces the electron density of Zn and O due to charge neutrality (Figure 4d). 25,38 Clearly, the Pd 3d 5/2 spectrum showed that the active metal existed in the form of Pd 2+ and was slightly shifted to a higher binding energy for 0.4% Pd/Zn(Al)O (10:1) (Figure 4e), possibly due to the metal−support interaction between the Pd and Pd/Zn(Al)O resulting from the metal vacancies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Most of these processes require high catalyst loadings along with thermal activation and/or toxic additives. 7–9 In addition, the above-mentioned homogeneous systems do not allow for the recovery of the catalysts, which can be costly especially when dealing with noble metals. In an effort to circumvent this shortcoming, heterogeneous systems have been developed by others more recently but again, elevated temperatures and/or high catalyst loadings are often required for an effective reaction to occur.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of secondary phosphine oxides to alkenes and alkynes represents a simple and straightforward approach to simultaneously create C–P and C–H bonds, with full atom economy. 4 The various hydrophosphinylation strategies that have been implemented so far include radical processes, 5 photo-activation, 6 and metal-catalyzed reactions 7 as described in seminal reports by Tanaka and co-workers. 8 However, most metal-catalyzed approaches rely on homogeneous metal complexes which are virtually impossible to recycle.…”
Section: Introductionmentioning
confidence: 99%
“…1a), which could be indexed to the (220) and (200) facets of the crystalline MgO (PDF #45-0946), respectively. 41 No diffraction peak ascribed to the metal Pt phase was detected, implying that the Pt species were highly distributed within the skeleton of MgO@C or their loadings are very low. Thermogravimetric analysis (TGA) revealed that MgO@C has thermal stability up to 600 K (Fig.…”
Section: Catalyst Characterizationmentioning
confidence: 99%